Pengolahan Kripik Singkong Aneka Rasa Berbasis Pangan Lokal Di Kabupaten Konawe Selatan - Rosmawaty, Rosmawaty; Yusria, Wa Ode; Maharani, Sri Wiyati (PROSIDING SEMINAR NASIONAL AGRIBISNIS, 2015)
The purpose of IbM of Cassava chips Various flavors at Lambusa Village South Konawe was to improved the quality of cassava chips in 2 (two) business group partners, increase marketing networks through improved packaging design in accordance with applicable regulatory standards, as well as improved the capacity of group cassava chips. The approaches used in this program are: (1) Method of Technology Transfer. This model is used to help the household industry business cassava chips in processing and production through develop appropriate technologies that are easy to obtain, easy to be operated and cheap so it can be reached by applying a good way of food production (CPMB) The process of production of cassava chips to be provided is a quality control technique of products ranging from raw materials to finished products, packaging and labeling, (2) method of entrepreneurship capacity building (ECB), which is helping home business industry of cassava chips in the form of professional entrepreneurial spirit, both in technical and management responsibilities . The results obtained from this IbM activities are: (1) technical and business management training to improve the quality, (2) improved packaging (3) the procurement of cassava slicer machine, (4) an increase in knowledge about the making report of cash flow, inventory and financial statements and the availability of report cash flow and inventory.